Novel regulators of planar cell polarity: a genetic analysis in Drosophila. - Weber, U.; Gault, W.J.; Olguin, P.; Serysheva, E.; Mlodzik, M. (Genetics, 2012)
Planar cell polarity (PCP) is a common feature of many epithelia and epithelial organs. Although progress has been made in the dissection of molecular mechanisms regulating PCP, many questions remain. Here we describe a screen to identify novel PCP regulators in Drosophila. We employed mild gain-of-function (GOF) phenotypes of two cytoplasmic Frizzled (Fz)/PCP core components, Diego (Dgo) and Prickle (Pk), and screened these against the DrosDel genome-wide deficiency collection for dominant modifiers. Positive genomic regions were rescreened and narrowed down with smaller overlapping deficiencies from the Exelixis collection and RNAi-mediated knockdown applied to individual genes. This approach isolated new regulators of PCP, which were confirmed with loss-of-function analyses displaying PCP defects in the eye and/or wing. Furthermore, knockdown of a subset was also sensitive to dgo dosage or dominantly modified a dishevelled (dsh) GOF phenotype, supporting a role in Fz/PCP-mediated polarity establishment. Among the new "PCP" genes we identified several kinases, enzymes required for lipid modification, scaffolding proteins, and genes involved in substrate modification and/or degradation. Interestingly, one of them is a member of the Meckel-Gruber syndrome factors, associated with human ciliopathies, suggesting an important role for cell polarity in nonciliated cells.